The Effect of a Training Programme (Skill-Psychological) on the Psychological Fitness and Performance of some Offensive skills of Volleyball Players - Al-Qaisi, Mayada Tahsin Abdulkarim (Pubmedia Jurnal Pendidikan Olahraga, 2024)
Volleyball is a competitive sport activity characterized by a direct struggle between two teams: Volleyball is one of the competitive sports activities that are characterized by direct struggle between two teams, as it has become a lot of practice today and occupies a good position as it is at a high and beautiful level of performance, so there is a desire for those who practice it to appear integrated performance as it is a combination of many different skills, whether offensive or defensive. Hence the importance of the research lies in knowing the extent of the effect of a training programme (skill - psychological) on psychological fitness and performance of some offensive skills in volleyball players. The issue lies in the fact that the player faces difficulties and psychological pressures during the match and his inability to regulate and control his emotions and greatly affect his performance, so the researcher decided to study the effect of a training programme (skill-psychological) on the psychological fitness and performance of some offensive skills in volleyball players. The aim is to find out the effect of a training programme on psychological fitness and performance of some offensive skills. It is hypothesized that there are statistically significant differences between the results of the pre and post tests in psychological fitness and the performance of some offensive skills in the sample. The experimental approach was used. The sample was volleyball players. It used the appropriate methods, tools and devices for research and also used the scale and tests and conducted pre and post tests and the exploratory and main experiment and the number of units was 16 units, two units per week, and concluded that the training exercises (skill - psychological) have a clear impact on the psychological fitness of players.